Tendencias espacio-temporales de los avistamientos de fauna marina en los buceos turísticos (Isla del Coco, Costa Rica) - Sibaja-Cordero, Jeffrey Alejandro (Revista de Biología Tropical, 2008)
Spatial-temporal tendencies of marine faunal observations in touristic dives (Isla del Coco, Costa Rica). Data on several marine species collected over 15 years (1991 to 2007), by dive-masters of the diving company Undersea Hunter, at 27 sites around Isla del Coco (Cocos Island), Pacific Costa Rica, were analyzed. The goal was to create a base line of the pelagic species that live in the waters of the Island based on reports of their activity during tourist dives. A data matrix was generated and multivariate methods used to determine the patterns of temporal and spacial variation. Variability in the occurrence of several species was high between sites. All sites presented a change in the asemblages during the 1991-92 and 1997-98 El Niño events. However, some sites had more influence by this climatic oscillation. El Niño event had stronger repercussion on the abundance and occurrence of particular species. Elasmobranchs such as the scalloped hammerhead sharks (Sphyrna lewini) and the marbled ray (Taeniura meyeni) showed a negative association with anomalous sea surface temperatures. Starting in 2000 there is a decrease in the average abundances and in the presence of the pelagic species, especially for economically important sharks. These variables reach similar values compared to those of El Niño years. A possible explanation is the increase of illegal fishing that took place around the Island or immediate waters. Some of these are species with great mobility. Nevertheless, some species had a small recovery in recent years. A collaborative program between the Government of Costa Rica and MarViva (a non governmental organization) in recent years has resulted in an improvement in the conservation of the marine fauna of Isla del Coco. Rev. Biol. Trop. 56 (Suppl. 2): 113-132. Epub 2008 August 29.